Malaysian mothers’ feeding practices, household food security and picky eating behaviour: lesson learnt from covid-19 pandemic - Yang, Wai Yew; Ung, Connie Kee Lee; Ong, Yi Xuan; Arasu, Kanimolli (University Putra Malaysia, 2024)
Introduction: Drastic changes in food access during the COVID-19 pandemic may impact families’ feeding practices, and eating behaviour. This study aimed to determine the association between maternal feeding practices, household food security status, and children’s picky eating among Malaysian mothers. Methods: A cross-sectional study was conducted virtually among 102 mothers with children aged from 5 to 12 years old (January-June 2022). Self-administered questionnaires on sociodemographic, feeding practices, household food security and child-picky eating behaviour were used. The statistical associations for key variables were analysed. Results: Most participants were Chinese mothers (87.3%) aged 30-39 years old (52.0%) with tertiary education (52.0%) and from middle to high household income (64.7%). Restriction domain had the highest median (interquartile range) score of 3.63 (1.00). A quarter of the household was experiencing food insecurity and about 34.3% of the children were classified as ‘picky eaters’. A significant difference was found for restrictive feeding practices and household food security status (3.75 (0.97) versus 3.13 (1.19), p=0.022), while mothers of picky eaters were more likely to pressure their children to eat compared to non-picky eaters (3.75 (0.75) versus 3.25 (1.00), p=0.01). Conclusion: Despite food secure status during the pandemic, two food parenting approaches (restriction and pressure to eat) were significantly associated with the household food security status and children’s picky eating behaviour. While the additional environmental stress from the COVID-19 pandemic could be transient, there should be consideration of the long-term impact of maternal feeding practices on the health and nutritional status of growing children.